2021
DOI: 10.1590/0001-3765202120201926
|View full text |Cite
|
Sign up to set email alerts
|

Anuran diversity in ponds associated with soybean plantations

Abstract: Anurans are considered one of the most threatened animal groups in the world. Agricultural activities are related to water pollution and contamination, which affects biphasic organisms such as amphibians. Brazilian soybean cultivation covers about 36 million hectares and encompasses many remaining ponds used as breeding sites for amphibians. In this study, we evaluated richness, abundance and composition of the anuran communities in ponds with different levels of association with soybean cultivation. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…There is an ongoing debate about wetlands' conversion to grow crops, but rice fields are sometimes considered supplementary habitats for aquatic species (Maltchik et al, 2017). Although there are similar deleterious impacts in both crops (agrochemicals, land preparation, vegetation homogenisation), soy fields pose a harsher environment for tadpoles when compared to rice fields (Cunha et al, 2021;Moreira et al, 2014). Because rice fields retained water during most of the cultivation cycle (sometimes also in the off-season), differences in land management may favour the dominance of ground-dwelling species with benthonic tadpoles.…”
Section: Discussionmentioning
confidence: 99%
“…There is an ongoing debate about wetlands' conversion to grow crops, but rice fields are sometimes considered supplementary habitats for aquatic species (Maltchik et al, 2017). Although there are similar deleterious impacts in both crops (agrochemicals, land preparation, vegetation homogenisation), soy fields pose a harsher environment for tadpoles when compared to rice fields (Cunha et al, 2021;Moreira et al, 2014). Because rice fields retained water during most of the cultivation cycle (sometimes also in the off-season), differences in land management may favour the dominance of ground-dwelling species with benthonic tadpoles.…”
Section: Discussionmentioning
confidence: 99%
“…Although the sampled ponds still host relatively diverse anuran assemblages, the surrounding landscape is highly altered with the wetlands being constantly drained and vegetation replaced by pastures and cropland, mainly soybean (Gallant et al, 2007;Souza et al, 2017). One of the few studies contrasting anuran assemblages in ponds within soybean plantations and adjacent ponds outside the plantation zone found that tadpole abundance and richness were considerably lower in ponds within plantations (Cunha et al, 2021). Thus, even though communities may still be diverse locally, at the regional scale the metacommunity formed by ponds may be highly threatened.…”
Section: Discussionmentioning
confidence: 99%
“…Anuros são um dos grupos mais ameaçados dentre os vertebrados devido a sua dependencia reprodutiva com água e sensibilidade á perturbação no ambiente em que estão inseridos (Cunha et al 2021), contudo estão entre os mais diversos, com aproximadamente 1.136 espécies reconhecidas (Segalla et al 2021). Além disso, muitas espécies de anfibios, principalmente da amazônia, ainda não foram descobertas ou aguardam reconhecimento taxonômico (Vacher et al 2020;Moura;Jetz 2021).…”
Section: Introductionunclassified